Dynamic social power modulates neural basis of math calculation - Harada, Tokiko; Bridge, Donna; Chiao, Joan Y. (Frontiers in Human Neuroscience, 2013)
Both situational (e.g., perceived power) and sustained social factors (e.g., cultural stereotypes) are known to affect how people academically perform, particularly in the domain of mathematics. The ability to compute even simple mathematics, such as addition, relies on distinct neural circuitry within the inferior parietal and inferior frontal lobes, brain regions where magnitude representation and addition are performed. Despite prior behavioral evidence of social influence on academic performance, little is known about whether or not temporarily heightening a person’s sense of power may influence the neural bases of math calculation. Here we primed female participants with either high or low power and then measured neural response while they performed exact and approximate math problems. We found that priming power affected math performance; specifically, females primed with high power performed better on approximate math calculation compared to females primed with low power. Furthermore, neural response within the left inferior frontal gyrus, a region previously associated with cognitive interference, was reduced for females in the high power prime compared to low power prime during approximate, but not exact, calculation. Taken together, these results indicate that even temporarily heightening a person’s sense of social power can increase their math performance, possibly by reducing cognitive interference during math performance.